(untitled) (Journal of NELTA, 2015)
Critical Pedagogy (CP), a mode of pedagogy, aims to empower learners and provide justice by offering preferential options and deconstructing authoritative and logo centric tendency in education. The current study, by using a mixed methodological design (qualitative and quantitative), illustrates a group of Nepali English language teachers’ attitudes regarding CP in ELT, focusing on how they employ CP in their classrooms. For this research, a sample of 10 teachers was purposively selected from Baitadi and Dadeldhura districts. Five teachers’ classes were observed. Analyzing the data collected through a survey questionnaire, it was found that all the teachers are in favour of CP in most cases in ELT. Even if all the teachers were notionally appeared in favor of practicing CP in most of the aspects that were asked to them, quite contrary to it, observation results of the teachers’ classes revealed that they did not, in any real sense, embrace CP in their teaching practice. Hence, this study invoked the ELT teachers to embrace CP practically in the classrooms. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12086 Journal of NELTA, Vol 19 No. 1-2, December 2014: 132-146